2021
DOI: 10.3390/antibiotics10111303
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Detection of Virulence-Associated Genes in Escherichia coli Strains Isolated from Commercial Broilers

Abstract: The aim of this study was to investigate the presence of iron-uptake and virulence genes, antibiotic resistance profiles, and phylogenetic relatedness in 115 Escherichia coli (E. coli) strains isolated from broilers in Slovakia and to determine their potential threat to human health. The most frequent phylogroups were B1 (37%) and A (21%), and 33.9% strains were included in pathogenic groups. The commonly observed iron-uptake genes were feoB (94%), sitA (83%), and iutA (58%). Protectins (iss, kpsMTII) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…2). The results agree with those of Kocúreková et al [16] in Slovakia who found Tobramycin E. coli resistance from broilers in 1.96%. The most common mechanism of acquired resistance to aminoglycosides is the modification of the chemical structure of the antibiotic by bacterial enzymes.…”
Section: Tobramycin E Coli Resistance Before Covid-19 Appearancesupporting
confidence: 92%
See 1 more Smart Citation
“…2). The results agree with those of Kocúreková et al [16] in Slovakia who found Tobramycin E. coli resistance from broilers in 1.96%. The most common mechanism of acquired resistance to aminoglycosides is the modification of the chemical structure of the antibiotic by bacterial enzymes.…”
Section: Tobramycin E Coli Resistance Before Covid-19 Appearancesupporting
confidence: 92%
“…Animal products may contain antimicrobial resistant bacteria as a result of fecal contamination during slaughter [32]. Commercial broilers can be reservoirs of virulent and resistant genes as well as Escherichia coli causing extra-intestinal infections, which can be a potential threat to humans via direct contact and food [16]. During the processing of meat, the bacteria from animal origin can contaminate other food items, the processing plant, or workers.…”
Section: Introductionmentioning
confidence: 99%